Sociological Trespasses: Interrogating Sin and Flesh - Aho, James (Lexington Books, 2011)
Racism, collective violence, sickness, environmental catastrophe, body obsession, greed, and accelerated life concern everyone. They are also the subject matter of this book. Here, however, they are not viewed as social problems to be solved by technical experts. Instead, they are viewed as products of the joint transference of aspects of ourselves onto objects independent of ourselves. More specifically, they emerge from conviction there is something 'out there'-say, a nation, an enemy, time, money, the environment, a medical cure, a bodily orifice (the mouth or genitals), a significant individual, or an anonymous public, etc.-the advancement of, accumulation of, defeat of, management of, or obeisance to can complete us, secure us, fill us, stabilize us, or in some other way enable us to escape from or deny our 'lack': our existential precariousness or death. Sociological Trespasses attempts to disillusion readers of this conviction. This is not done for itself, but to create space for imagining new horizons of lived-possibility, such as tolerance of human difference, simplicity, slowness, care, and wakefulness.